ZnO/Zn(OH)2 nanoparticles and self-cleaning coatings for the photocatalytic degradation of organic pollutants - Faheem, Muhammad; Siddiqi, Humaira M.; Habib, Amir; Shahid, Muhammad; Afzal, Adeel (Frontiers in Environmental Science, 2022)
Zinc oxide (ZnO) nanostructures have emerged as efficient heterogeneous photocatalysts for the degradation of organic pollutants in aqueous solutions and industrial wastewaters. In this work, a simple and effective method is reported for the synthesis of zinc oxide/zinc hydroxide (ZnO/Zn(OH)2) hybrid nanoparticles using a mineral acid to enhance the photocatalytic activity of ZnO. Infrared spectroscopy reveals the presence of hydroxyl groups in ZnO/Zn(OH)2 nanoparticles. X-ray diffraction shows the formation of hexagonal wurtzite ZnO nanoparticles, which retain their wurtzite structure after acid treatment but additional diffractions for Zn(OH)2 are also recorded. The optical bandgap of resulting ZnO and ZnO/Zn(OH)2 nanoparticles is reduced to 3.05 and 3.08 eV, respectively. In the initial photocatalysis experiments, ZnO/Zn(OH)2 nanoparticles exhibit 3.5-times improved degradation and removal of sunset yellow dye, a model organic pollutant, from deionized water compared to pristine ZnO nanoparticles. Hence, for further studies, ZnO/Zn(OH)2 coatings are fabricated on glass slides with a uniform surface morphology as shown by the atomic force microscopy. The time-dependent UV-visible spectroscopy reveals the photocatalytic degradation of sunset yellow over the surface of ZnO/Zn(OH)2 coatings. The degradation reaction follows the pseudofirst-order mechanism with a rate constant of 2.9 × 10–2 min−1. The recyclability and stability experiments reveal the retention of appreciable photocatalytic activity of ZnO/Zn(OH)2 coatings (with >92% degradation efficiency after six successive cycles). The results are compared with recent examples from the pertinent literature. The surface hydroxyl groups on ZnO/Zn(OH)2 nanoparticles and bandgap lowering enhance the anchoring of dye molecules and electron transfer reactions.